2008
DOI: 10.1111/j.1600-0846.2008.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Topically applied growth factors change skin cytoplasmic creatine kinase activity and distribution and produce abnormal keratinocyte differentiation in murine skin

Abstract: The skin PCR/CPK system is affected by growth factors. Furthermore, this system appears to play an important role, both in the normal physiology of skin and pathophysiological conditions such as psoriasis and carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Because some malignant cells have receptors for certain GFs, and some GFs may increase cellular proliferation, there has been concern as to whether GFs might have the potential for tumorigenesis or promotion of cellular atypia. 55,56 Others postulate that exogenous GFs have a normalizing effect on the growth and differentiation of target cells. Studies of the effects of individual GFs on animal skin and on human tumor cells have shown conflicting results.…”
Section: Adverse Effects and Safety Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because some malignant cells have receptors for certain GFs, and some GFs may increase cellular proliferation, there has been concern as to whether GFs might have the potential for tumorigenesis or promotion of cellular atypia. 55,56 Others postulate that exogenous GFs have a normalizing effect on the growth and differentiation of target cells. Studies of the effects of individual GFs on animal skin and on human tumor cells have shown conflicting results.…”
Section: Adverse Effects and Safety Considerationsmentioning
confidence: 99%
“…EGF and TGF-α both induced a transition from the CPK MM to CPK BB isoenzyme. 56 The significance of these findings is that the phosphocreatine/CPK system is believed to play an important role in the normal physiology of skin and in pathophysiological conditions such as psoriasis and carcinogenesis. Histopathological evaluation showed abnormal differentiation and distribution of keratinocytes.…”
Section: Adverse Effects and Safety Considerationsmentioning
confidence: 99%